Răspunsuri

2014-07-03T11:28:29+03:00
1) x²+4x-x-4 +2x ²- 4x+x-2=3x²-6
2)x ³+ x²-2x-2+x ³-4x+x²-2x-x+2=2x³+2x ²-9x
3)x ³-2x²-3x²+6x-x la 3-2x²+2x la 3+2x²=2x la 3+5x ²+7x+1 
Cel mai inteligent răspuns!
2014-07-03T11:30:20+03:00
1)
(x - 1)(x + 4) + (2x + 1)(x-2) = 
+3x - 4 + 2x² - 3x - 2 = 3x² - 6

2)
  (x²-2)(x+1)+x(x²-4)+(x-1)(x-2)=
x³ + x²  -  2x -2     + x³ - 4x     +      x² - 3x + 2 =
2x³  + 3x²  - 9x  

3)  
(x²-3x)(x-2)    -x²(x+2)  +(2x²+1)(x+1)=

-3x²- 2x² + 6x   - - 2x²  + 2x³  + 2x²  + x  + 1 = 
= 2x³ - 2x² + 7x + 1